Data Warehouse for Study Program Accreditation Data Management at Private University X - Tifani Anasya Putri; Jap Tji Beng; Dedi Trisnawarman; Sri Tiatri; Fouad Nagm; Michael S. Naidas; Tasya Mulia Salsabila; Rahmiyana Nurkholiza (STMIK Banjarbaru, 2025)
Technological advancements in the Fourth Industrial Revolution have transformed higher education, yet accreditation processes often suffer from inefficient data management, causing delays, inconsistencies, and limited monitoring of performance indicators. This study designs a data warehouse integrated with a dashboard and Early Warning System (EWS) to improve accreditation data management at University X, West Jakarta. Using Kimball’s Dimensional Model, data were structured into fact and dimension tables, with collection methods including interviews with the Head of the IT Department and document analysis of accreditation processes. Descriptive statistics were applied to identify trends and patterns. The dashboard enables real-time visualisation of key metrics, while the EWS issues alerts on missing or outdated data. Results show that the snowflake schema enhances data organisation and clarity, reducing manual processing and facilitating proactive monitoring. The system supports more efficient accreditation management and strengthens institutional readiness for assessment.